TINGKAT KEPUASAN PETANI TERHADAP KINERJA PENYULUH PERTANIAN LAPANGAN (PPL) DI DESA HUMBOTO KECAMATAN UEPAI KABUPATEN KONAWE - Ngatini, Ngatini; Embe, Wa; Rosmalah, Sitti (Agros Journal of Agriculture Science, 2024)
farmer satisfaction in obtaining services from their field extension workers. An agricultural extension worker must know the level of satisfaction of the extension target, namely farmers in their work area, in order to improve the quality and performance and success of their extension activities in the future. For farmers in Humboto Village, Uepai District, Konawe Regency, the presence of agricultural extension workers is highly expected, especially to help farmers solve the problems they face, but in reality, not all farmer problems can be resolved. Agricultural extension workers in Humboto Village, Uepai District, number 1 extension worker who also works in other villages because the extension workers from the State Civil Apparatus (ASN) are still very few, namely 8 people who have to work in 18 villages in Uepai District (BPP Uepai District, 2024). The lack of extension workers with a fairly large area of work can affect the quality of work (performance) of agricultural extension workers. Therefore, the purpose of this study was to analyze the level of farmer satisfaction with the performance of extension workers in Humboto Village, Uepai District. Uepai, Konawe Regency. The attributes used to measure the level of farmer satisfaction are 5 attributes with 20 items. Data analysis used a score based on a Likert scale with 5 categories, namely very satisfied, satisfied, quite satisfied, dissatisfied and very dissatisfied. The results showed that the level of farmer satisfaction in Humboto Village, Uepai District, Konawe Regency is in the category of quite satisfied with the performance of PPLKey-words:  satisfaction; performance; PPL